2000
DOI: 10.1161/01.str.31.2.476
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Thigh Cuff Technique for Measurement of Dynamic Cerebral Autoregulation

Abstract: Background and Purpose-Dynamic methods of measuring cerebral autoregulation have become an accepted alternative to static evaluation. This article aims to describe a set of data collected from healthy volunteers by a dynamic method, the purpose being to qualify and quantify expected results for those who may be designing a study using this technique. Methods-Cerebral blood flow velocity (CBFV) (measured by transcranial Doppler) and arterial blood pressure (Finapres) were recorded in 16 normal subjects before, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
114
1
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(129 citation statements)
references
References 31 publications
9
114
1
5
Order By: Relevance
“…25 Studies in humans have shown that ARI is constant in the order of 5 ± 1 in neurologically healthy, awake patients. 11,24 The patients studied in the present investigation did not present with a medical history or clinical signs of cerebrovascular disease. We, therefore, assumed intact autoregulation in these patients and baseline measurements in awake patients were considered avoidable in order to reduce the preoperative psychological strain.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…25 Studies in humans have shown that ARI is constant in the order of 5 ± 1 in neurologically healthy, awake patients. 11,24 The patients studied in the present investigation did not present with a medical history or clinical signs of cerebrovascular disease. We, therefore, assumed intact autoregulation in these patients and baseline measurements in awake patients were considered avoidable in order to reduce the preoperative psychological strain.…”
Section: Discussionmentioning
confidence: 97%
“…For example, any recovery of CBFV independent of MAP results in incremental steps of the CBFV curve and translates to an ARI of 4-6 indicating intact cerebrovascular autoregulation. 11 A pressure passive CBFV-pattern equals no difference between the CBFV and the MAP curve and translates to an ARI of 0 (=no autoregulation).…”
Section: Discussionmentioning
confidence: 99%
“…However, this transient effect stems naturally from the phase dynamics and does not have a pathological origin. The insight provided by the synchrony analysis may also allow to put in different perspective the reports of the very low values of ARI autoregulation index in healthy individuals (18). The low values of this index would suggest the absence of autoregulatory response in physiological condition.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown considerable intra-subject variation for repeated thigh cuff tests [33], repeated recordings with spontaneous fluctuations [22,25] as well as recordings with controlled breathing where a sliding window was used to estimate short-term variability [25].…”
Section: Intra-subject Variabilitymentioning
confidence: 99%
“…Previous analyses that concentrated on the performance of the ARI [25,32,33] have shown large variations over time and sudden drops to zero of this index. Although rigorous studies have not been performed to understand the source of this variability, this may be due to the constraint that the Aaslid's model [15] imposes on the index as it only uses a set of ten filters [25].…”
Section: Intra-subject Variabilitymentioning
confidence: 99%